(untitled) (Journal of Business and Management Research, 2016)
The impact of Chief Executive Officer (CEO) leadership style on the profitability of an organization has been a major concern of much academic research work in the past. However, there seems to be no consensus on this issue. It is generally believed that leaders influence organizational performance through those they lead. Therefore, employee job satisfaction is hypothesized to have a mediating effect on the relationship between the CEO leadership style and the profitability of an organization. This study, conducted among 136 employees of 17 finance companies in Nepal during December 2013, found a very weak relationship between the CEO leadership style and the profitability of an organization. The study also refuted the mediating effect of job satisfaction on the relationship between the CEO leadership style and the profitability of an organization. The findings support the contextualists view on the leadership-performance debate. The probable reasons and implications of the findings are discussed. Journal of Business and Management Research Vol.1(2) 2016, pp.1-16